2017
DOI: 10.1073/pnas.1702251114
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Myo7b/USH1C complex suggests a general PDZ domain binding mode by MyTH4-FERM myosins

Abstract: Unconventional myosin 7a (Myo7a), myosin 7b (Myo7b), and myosin 15a (Myo15a) all contain MyTH4-FERM domains (myosin tail homology 4-band 4.1, ezrin, radixin, moesin; MF) in their cargo binding tails and are essential for the growth and function of microvilli and stereocilia. Numerous mutations have been identified in the MyTH4-FERM tandems of these myosins in patients suffering visual and hearing impairment. Although a number of MF domain binding partners have been identified, the molecular basis of interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 61 publications
2
61
0
Order By: Relevance
“…1A) (Pickles et al, 1984). Collectively, this work has shown that the MyTH4-FERM tail domain of the motor protein Myo7a is essential to form a stable ternary complex with the PDZ-domain-containing scaffolding proteins USH1C (harmonin) and scaffold protein containing ankyrin repeats and SAM domain (SANS, also called USH1G) to bind the cytoplasmic tail of the cadherin CDH23 (Caberlotto et al, 2011;Grati and Kachar, 2011;Li et al, 2017). In addition, the extracellular region of the cadherin dimer interacts with the extracellular region of the protocadherin PCDH15 dimer on a neighboring stereocilium (Siemens et al, 2004).…”
Section: Apical Membrane Morphology: the Cell Polarity Program And Mementioning
confidence: 90%
“…1A) (Pickles et al, 1984). Collectively, this work has shown that the MyTH4-FERM tail domain of the motor protein Myo7a is essential to form a stable ternary complex with the PDZ-domain-containing scaffolding proteins USH1C (harmonin) and scaffold protein containing ankyrin repeats and SAM domain (SANS, also called USH1G) to bind the cytoplasmic tail of the cadherin CDH23 (Caberlotto et al, 2011;Grati and Kachar, 2011;Li et al, 2017). In addition, the extracellular region of the cadherin dimer interacts with the extracellular region of the protocadherin PCDH15 dimer on a neighboring stereocilium (Siemens et al, 2004).…”
Section: Apical Membrane Morphology: the Cell Polarity Program And Mementioning
confidence: 90%
“…Of note, the causative genes for three USH1 subtypes (USH1E, USH1K and USH1H) still have not been identified, suggesting that more Usher complex components may remain to be discovered (17)(18)(19). A similar situation is seen with the IMAC; structure-function studies of this complex clearly point towards the idea that the full interactome is not yet known (5,20,21).…”
Section: Introductionmentioning
confidence: 93%
“…Immunostaining studies showed that Myosin VIIA (MYO7A), USH1G (also known as Sans), and USH1C (also known as Harmonin or autoimmune enteropathy-related 75-kDa antigen ) are located at the UTLD, suggesting that they are involved in the electron-dense plaque formation, although the mechanism underlying the dense assembly formation is not understood (Grati and Kachar, 2011;Grillet et al, 2009). MYO7A, USH1G, and USH1C form a very stable tripartite complex via several pairs of specific interactions (Adato et al, 2005;Li et al, 2017;Pan and Zhang, 2012;Wu et al, 2011;Yan et al, 2010;Yu et al, 2017). The cytoplasmic tail (CT) of CDH23 interacts with USH1C (Pan et al, 2009;Siemens et al, 2002), thus linking the tail of the upper tip-link to UTLD ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…The cadherin-related family member 2 (CDHR2, also known as protocadherin 24) and cadherin-related family member 5 (CDHR5, also known as mucin-like protocadherin) interact in trans to form the filamentous tip-link (Crawley et al, 2014b). The CT of CDHR2 is coupled to the actin filaments via a tripartite complex composed of Myosin VIIB (MYO7B), USH1C, and ANKS4B (Crawley et al, 2014b(Crawley et al, , 2016Li et al, 2016aLi et al, , 2017Weck et al, 2016;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%